2016
DOI: 10.2337/db16-0052
|View full text |Cite
|
Sign up to set email alerts
|

Inositol-Requiring Enzyme 1 Facilitates Diabetic Wound Healing Through Modulating MicroRNAs

Abstract: Diabetic skin ulcers represent a challenging clinical problem with mechanisms not fully understood. In this study, we investigated the role and mechanism for the primary unfolded protein response (UPR) transducer inositol-requiring enzyme 1 (IRE1α) in diabetic wound healing. Bone marrow–derived progenitor cells (BMPCs) were isolated from adult male type 2 diabetic and their littermate control mice. In diabetic BMPCs, IRE1α protein expression and phosphorylation were repressed. The impaired diabetic BMPC angiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 58 publications
2
76
0
Order By: Relevance
“…miRNAs control diverse pathways depending on cell types and micro-environment. Of particular note, pre-miRNAs have been reported to be RNA cleavage substrates of the IRE1α RNase activity through the RIDD pathway (10, 24). Here, we investigated whether the IRE1α-miRNA regulatory pathway is involved in hepatic lipid metabolism and hepatic steatosis and found that IRE1α deficiency affects the biogenesis of select miRNAs and, consequently, the abundance of metabolic enzymes that increase hepatic lipid accumulation that contributes to hepatic steatosis.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs control diverse pathways depending on cell types and micro-environment. Of particular note, pre-miRNAs have been reported to be RNA cleavage substrates of the IRE1α RNase activity through the RIDD pathway (10, 24). Here, we investigated whether the IRE1α-miRNA regulatory pathway is involved in hepatic lipid metabolism and hepatic steatosis and found that IRE1α deficiency affects the biogenesis of select miRNAs and, consequently, the abundance of metabolic enzymes that increase hepatic lipid accumulation that contributes to hepatic steatosis.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, this mechanism leads to an increase in collagen deposition and organization in the healing wound (allowing also elastin deposition), and this positive feedback‐loop improved the histological features and the quality of the regenerated skin tissue, as showed by the increase of the maximum tolerated load. At 14 days, an increased expression of Ang‐1 was observed, especially with anti‐miR200b alone or in co‐administration and this could be due to the fact that Ang‐1 mRNA is a specific target of miR200b (Wang et al, ). Ang‐1 decreases during the early stages of angiogenesis, thus destabilizing the vessels so that the endothelial cells are able to start sprouting (Staton et al, ) and, later on, its expression has to increase so that newly formed vessels are stabilized.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, our results did not show that anti‐miRs can also increase production of mRNA, a possible explanation of our observation of an increase in protein levels that was not always matched by the corresponding mRNA. The increase in Ang‐1 and Tek is not surprising, as HIF‐1α increases their transcription (Krock et al, ) and miR15b targets HIF‐1α mRNA, while miR200b specifically targets Ang‐1 mRNA (Wang et al, ), It is therefore very likely that the combined inhibition of the two miRNAs caused the observed increase.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of IRE1 signaling decreases glioma vascular density and vessel perfusion in vivo, which are rescued by the expression of a transgene of IL-6 [41]. Interestingly, in diabetic bone marrow-derived progenitor cells, loss of IRE1 results in decreased angiopoietin 1 expression and disrupts angiogenesis, due to inefficient RIDD of miR-466 and miR-200 families [107]. In line with this observation, the PERK/ATF4 pathway regulates the angiogenic switch in human tumors, by increasing the expression of many proangiogenic modulators, including VEGF, FGF-2, and IL-6, with the concomitant decrease in the expression of the angiogenic inhibitors THBS1, CXCL14, and CXCL10 mRNA [108].…”
Section: Upr and Angiogenesismentioning
confidence: 99%